Assessing the current conditions of weather and climate information services in East Africa: Household survey - Mvuyibwami, Patrick; Kagabo, Desire M; Byandaga, Livingstone; Eitzinger, Anton; Karanja, David; Unnuarite, Uwera; Ssekandi, Wilber; Nkalubo, Stanley; Mbiu, Julius; Dushimirimana, Eric; Muhigirwa, Mirreille U; Nchanji, Eileen; et al. (2024)
The Enhancing Climate Resilience in East Africa (ECREA) project seeks to strengthen resilience by improving access to Weather and Climate Information Services (WCIS) and Impact-Based Early Warnings (IBEWs) tailored for farming communities. A baseline household survey involving over 800 participants across Uganda, Rwanda, Kenya, and Tanzania examined adaptive capacity, resilience, and access to these services. Findings revealed gender and education disparities, limited livelihood diversification, and uneven access to WCIS and IBEWs, particularly among women, smallholder, and low-education-level farmers. While use of these services was associated with modest improvements in yields, damage reduction, and avoided losses, gaps in inclusivity, precision, and timeliness limit their effectiveness. The results underscore the need for gender-responsive, context-specific, and accessible climate information services to enhance equitable adaptation outcomes across the region.